2004
DOI: 10.1590/s0021-75572004000800007
|View full text |Cite
|
Sign up to set email alerts
|

Mineralização óssea em adolescentes do sexo masculino: anos críticos para a aquisição da massa óssea

Abstract: Objective: To verify the behavior of the mineral bone content and density in male adolescents according to age and secondary sexual characters.Methods: 47 healthy adolescents between 10 and 19 years old were assessed according to weight, height, body mass index, puberty stage, calcium intake, bone mineral density and content in the lumbar spine and in the proximal femur. The bone mass was measured through bone densitometries. The intake of calcium was calculated through a 3-day diet. The BMI (body mass index) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
6
0
14
Order By: Relevance
“…DISCUSSãO Indivíduos cuja faixa etária está entre 13 e 17 anos são caracterizados pela rá-pida aquisição de conteúdo mineral ósseo. Nessa fase, ocorre o pico de massa óssea, que é quando o processo de formação sobrepuja o de reabsorção óssea (PhilliP;lazar, 2003;silva et al, 2004;Pettersson et al, 2000). Astrand (1992) complementa que indivíduos dessa faixa etária, tanto no aspecto funcional quanto no aspecto estrutural, não são semelhantes aos adultos.…”
Section: Resultsunclassified
“…DISCUSSãO Indivíduos cuja faixa etária está entre 13 e 17 anos são caracterizados pela rá-pida aquisição de conteúdo mineral ósseo. Nessa fase, ocorre o pico de massa óssea, que é quando o processo de formação sobrepuja o de reabsorção óssea (PhilliP;lazar, 2003;silva et al, 2004;Pettersson et al, 2000). Astrand (1992) complementa que indivíduos dessa faixa etária, tanto no aspecto funcional quanto no aspecto estrutural, não são semelhantes aos adultos.…”
Section: Resultsunclassified
“…Only two studies evaluating these aspects were found until now. One study only included adolescent boys 11 , whereas the other evaluated adolescents of both genders ranging in age from 6 to 14 years 12 . Therefore, the objective of the present study was to characterize bone mineral content (BMC) and BMD in adolescent girls according to age and pubertal stage.…”
Section: Introductionmentioning
confidence: 99%
“…7 In a recent study with Brazilian adolescents, the authors have described a remarkable increase in bone mineralization as a result of sexual maturation, pubertal stage above grade IV and age older than 14-15 years. 8 Approximately 85-90% of the final bone mass in adults is achieved up to the age of 18 years in girls and up to the age of 20 in boys. From then on, it remains constant up to the fourth decade of life, when there is gradual physiological loss due to the advancement of age.…”
Section: Introductionmentioning
confidence: 99%